Technology disaster response and recovery planning - Mallery, Mary (London, England : Facet Publishing, 2015)
As libraries depend more and more on technology to provide essential services, they need to create a comprehensive response and recovery plan in the event of floods, fire, or other natural-- or man made-- disasters. This guide includes lessons learned from successful efforts in providing digital continuity and recovering from a variety of situations.
Includes bibliographical references and index.
Keywords: Library buildings -- Safety measures -- Planning; Libraries -- Information technology -- Security measures -- Planning; Library materials -- Conservation and restoration -- Planning